Estudo de ferramentas de automação para computação em nuvem - Mattioli, Matheus Teixeira (Universidade Federal de São Carlos, 2023)
Computing emerged to facilitate the actions of human life, from the creation of electronic spreadsheets to information access. Bringing it to cloud computing, it offers solutions such as virtual services to facilitate access by companies or users to persistent remote storage or even infrastructure. For example, one can consider a remote location for storing files, or a distant infrastructure that can be used in some virtual application. Aiming to build a structure that offers cloud computing, this work proposes studying and implementing automation techniques for cloud environments. Making use of techniques such as infrastructure as code and metal as a service, the objective is automating this implementation, making it fast and scalable, something that is essential in the modern world. As a result, we present a study on the use of the main open source tools available as open software.
A study on cloud computing automation tools
Keywords: Computação em nuvem; Cloud computing; Infraestutura como código; IaC; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO